PERBEDAAN WAKTU REAKSI DAN TINGKAT KELELAHAN ANTARA PEKERJA SHIFT PAGI DAN SHIFT MALAM - Rianti, Olivia Dewi; Fakhrurazzy, Fakhrurazzy; Triawanti, Triawanti (Jurnal Berkala Kedokteran, 2015)
Fatigue is a feeling of weariness or lack of energy that does not decrease when a person rests. The main reason of occupational accidents caused by humans is stress and fatigue. This study aims to analyze the differences of reaction time and fatigue stage between morning shift workers and night shift workers of coal mining department operators in PT. Kaltim Prima Coal. This research was an analytic observational research with cross sectional approach and purposive sampling technique. Data taken from 30 workers of morning shift and 30 workers of night shift who fulfill the inclusion criteria. The results showed that the average reaction time of morning shift workers was 0.81 seconds and 0.89 seconds for night shift workers. The results of questionnaire showed amount of very tired worker category, tired, and less tired on the morning shift workers for each category were 7, 21, and 2, while the night shift workers for each category were 3, 25, and 2. Results of unpaired t-test for reaction time showed no significant difference (p = 0.2) and the results of the Kolmogorov-Smirnov test for fatigue stage showed no significant difference (p = 0.952) between the morning shift workers and night shift workers of mining coal department operators in PT. Kaltim Prima Coal.Â Keywords: Reaction time, fatigue stage, shift workers